Criteria for urban sprawl / land use expansion - Yaakup, Ahris; Muhammad Ludin, Ahmad Nazri (Faculty of Built Environment, 2008)
The vast growth of development in urban ares without control was spread out to urban finge and become a sprawl. In the other hands, sprawl is a term commonly used to describe one or both of the several phenomena. Firstly, the phenomena where development far beyond a region’s historic core, the type of sprawl is not growth. Growth is an increase in number of people in place. The sprawl is just the redistribution of those people from one place to another. Secondly, the development that is extremely automobile-oriented that is usually due to street patterns and/or design that encourage walking and very low density. There are three types of urban sprawl which is low-density continuous sprawl, ribbon sprawl, and leapfrog development sprawl. The sprawl city causes of several effects, there are four indicators that express socioeconomic changes related to sprawling which are migration, urbanization level, non-agricultural labour force, and rural industrialization. Migration as a percentage of population related to immigration or emigration of inhabitants. The urbanization level is a proportion of urban population with regard to total population and the non agricultural labor force as the percentage of employment in industrial and services activities. The environmental impact of sprawl spans local, regional, and global geographical scales. For example, the cumulative effect on energy consumption and air pollution of individual suburbanites and exurbanites commuting back and forth to work are considerable and global in significance. Using the Analyical Hierarchy Process (AHP), this research purposed to come out with the list of criteria influencing urban sprawl and classification of factors based on weight of contribution significance.